2022
DOI: 10.3390/jcm11082219
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Myocarditis and Pericarditis in Post COVID-19 Unvaccinated Patients—A Large Population-Based Study

Abstract: Myocarditis and pericarditis are potential post-acute cardiac sequelae of COVID-19 infection, arising from adaptive immune responses. We aimed to study the incidence of post-acute COVID-19 myocarditis and pericarditis. Retrospective cohort study of 196,992 adults after COVID-19 infection in Clalit Health Services members in Israel between March 2020 and January 2021. Inpatient myocarditis and pericarditis diagnoses were retrieved from day 10 after positive PCR. Follow-up was censored on 28 February 2021, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 32 publications
(38 reference statements)
0
41
1
Order By: Relevance
“…In our study cohort, chest pain was reported in just above one third of patients while acute pericarditis was diagnosed in 22%, which suggests that pericarditis could be an underdiagnosed disease, and therefore not optimally managed. There was a discrepancy between the relatively high occurrence of pericarditis in our long COVID-19 patients and that reported in a large study performed in post COVID-19 unvaccinated patients, where the incidence was very low [ 30 ]. Possible explanations for the latter finding is that post COVID-19 patients are intrinsically different from those with long COVID-19 syndrome.…”
Section: Discussioncontrasting
confidence: 88%
“…In our study cohort, chest pain was reported in just above one third of patients while acute pericarditis was diagnosed in 22%, which suggests that pericarditis could be an underdiagnosed disease, and therefore not optimally managed. There was a discrepancy between the relatively high occurrence of pericarditis in our long COVID-19 patients and that reported in a large study performed in post COVID-19 unvaccinated patients, where the incidence was very low [ 30 ]. Possible explanations for the latter finding is that post COVID-19 patients are intrinsically different from those with long COVID-19 syndrome.…”
Section: Discussioncontrasting
confidence: 88%
“…In France in 2021, the difference in myocarditis rate with 2019 and 2020 coincided with the vaccination campaign in young individuals (Boudemaghe et al, 2022). In a retrospective Israeli study based on a cohort of 196,992 adults, no increased incidence of pericarditis or myocarditis was observed after COVID-19 infection (Tuvali et al, 2022). In a cohort of 23 million people, in men over 12 years of age, the incidence of myocarditis/pericarditis in the unvaccinated was 0.261/100,000 people and shown to vary according to the vaccination schedule: between 0.322/100,000 people (1 dose of Moderna) and 2.402/100,000 people (1 dose of P zer followed by one dose of Moderna) (Karlstad et al, 2022).…”
Section: Post-vaccination Cardiovascular Aesmentioning
confidence: 95%
“…22 However, trial data demonstrating that vaccination reduces the risk of myocarditis in subsequent infection is elusive, and in fact the risks may be additive. Incidence of myocarditis rocketed from spring 2021 when vaccines were rolled out to the younger cohorts having remained within normal levels for the full year prior, despite COVID-19, 23 with the most up-to-date evidence, a paper from Israel 24 found that the infection itself, prior to rollout of the vaccine, conferred no increase in the risks of either myocarditis or pericarditis from COVID-19, strongly suggesting that the increases observed in earlier studies were because of the mRNA vaccines, with or without COVID-19 infections as an additional risk in the vaccinated. 24 Indeed, this reflects my own clinical experience of advising and managing several patients in the community who presented with a clear suggestion from the history of myocarditis post mRNA vaccination but aren't necessarily unwell enough to require hospital admission.…”
Section: Figurementioning
confidence: 99%
“…Incidence of myocarditis rocketed from spring 2021 when vaccines were rolled out to the younger cohorts having remained within normal levels for the full year prior, despite COVID-19, 23 with the most up-to-date evidence, a paper from Israel 24 found that the infection itself, prior to rollout of the vaccine, conferred no increase in the risks of either myocarditis or pericarditis from COVID-19, strongly suggesting that the increases observed in earlier studies were because of the mRNA vaccines, with or without COVID-19 infections as an additional risk in the vaccinated. 24 Indeed, this reflects my own clinical experience of advising and managing several patients in the community who presented with a clear suggestion from the history of myocarditis post mRNA vaccination but aren't necessarily unwell enough to require hospital admission. A very fit lady in her 50s developed fatigue and shortness of breath on exertion a few weeks after her second Pfizer injection.…”
Section: Figurementioning
confidence: 99%